Introduced or established? Convergent evidence indicates imported pine wood nematode vectors occupy gaps in native distribution - Jean-Claude Grégoire; Jean Artois; Julien Claude; Marius Gilbert; Serge Morand; Géraldine Roux; Gilles San Martin; Dimitrios Avtzis; Nick Berkvens; Jochem Bonte; Hans Casteels; Sandra Closa; et al. (Journal of Pest Science, 2026)
Monitoring regulated quarantine plant pathogens and, when relevant, their vectors is compulsory in the European Union. Local Monochamus species (Coleoptera, Cerambycidae) vector the pine wood nematode, Bursaphelenchus xylophilus , a non-native pest already established in most of Portugal. Only 29 M. galloprovincialis individuals were trapped in Belgium in ten years (2013–2022), despite a dense coverage of pheromone-baited traps, suggesting absence or a very rare local occurrence in the country. In the northern neighbouring countries, only one single established population is known in The Netherlands and one in Denmark. A species distribution model based on pheromone-trap catches (negative and positive) of M. galloprovincialis from 4,914 traps in 29 European countries between 2008 and 2019 was developed, using the overall climate conditions and the distribution of seven pine tree species as explanatory variables. The effect of spatial scale was tested with a multi-scale approach. With a 225*225 km spatial grain, the major explanatory variables were the mean diurnal temperature range and, to a lesser extent, the presence of Pinus spp. The model predicted a low probability of presence in Belgium, the Netherlands, Great Britain and north-western Germany compared to southern Europe. Genotyping allowed to conclude that at least some of the beetles caught in Belgium originated from foreign locations. All catches were located close to entry points, suggesting introduction with imported material. The small size of most of the Belgian pine stands may also explain the absence or apparently transient status, or rareness of Monochamus spp. This study thus suggests that surveys in Belgium should privilege entry points rather than local forest stands.

Synergistic negative effects of ash dieback and Armillaria root rot on health and stability of mature ash trees - Philipp Spiegel; Thomas Hintze; Aaron Kopp; Mario Sahli; Andreas Detter; Valentin Queloz; Simone Prospero; Renate Heinzelmann (Forest Ecology and Management, 2025)

Fishing for Phytophthora in watercourses of the highly urbanized Swiss Plateau - Corine N. Schoebel; Simone Prospero; Daniel Rigling; Beat Ruffner (Mycological Progress, 2024)
Phytophthora species are a cause for concern due to their invasive potential and the damage they can cause in agriculture, forestry, and natural ecosystems worldwide. Since water plays a crucial role in their dispersal, stream and river baiting is commonly used to survey risk areas for the presence of quarantine Phytophthora species. However, our understanding of the distribution and diversity of Phytophthora species in European watercourses remains incomplete. This study investigated the presence and diversity of Phytophthora species in Swiss watercourses, with a focus on the highly urbanized Swiss Plateau. Over the period 2012–2016, we sampled 32 watercourses, including major rivers and smaller streams. We isolated Phytophthora on selective media and sequenced the internal transcribed spacer region to identify the species. We recovered 241 Phytophthora isolates, representing 11 species from five major clades. Phytophthora clade 6 prevailed, with P. lacustris being the most common, found in 94.7% of the watercourses. The number of Phytophthora species per watercourse ranged from one to five, with no correlation to watercourse complexity. Our study reveals the presence of six previously unreported species in Switzerland, while known invasive species were not found. Watercourses appear less suited to detect invasive pathogenic Phytophthora species with a still limited distribution in the environment.

The Biosecurity Risks of International Forest Tree Seed Movements - Iva Franić; Michelle Cleary; Ayşe Gülden Aday Kaya; Helena Bragança; Guro Brodal; Thomas L. Cech; Anne Chandelier; Tuğba Doğmuş-Lehtijärvi; René Eschen; Asko Lehtijärvi; Michael Ormsby; Simone Prospero; et al. (Current Forestry Reports, 2023)
Purpose of Review Because tree seeds have been considered a low-risk pathway for the spread of plant pathogenic fungi, their international movement is not subject to strict phytosanitary regulation. However, recent studies have provided scientific evidence that the biosecurity risk of seed trade may not be as negligible as assumed. This review summarises current knowledge about seed trade activity across the world and seed-borne plant pathogenic fungi and highlights knowledge gaps that need to be filled to mitigate the risk of spreading tree pathogens via seeds. Recent Findings Several outbreaks of severe tree diseases in natural forests and plantations worldwide have been linked to fungal pathogens spread by seed trade. Indeed, recent studies based on modern sequencing technologies have shown that tree seeds harbour highly diverse fungal communities, including well-known pathogens and fungal taxa belonging to unknown species. While it has become clear that even apparently healthy seeds can carry potentially pathogenic fungi, the likelihood of seed-borne pathogens being introduced and becoming established, spreading and causing impact in the new environment is still unclear which challenges the assessment of the phytosanitary risk posed by seed trade. Summary Our analyses show that large amounts of tree seeds have been traded among countries and continents. Based on published literature, the risk of spreading pathogenic fungi via tree seed movement is high. However, the role of the taxonomically and functionally diverse fungal communities associated with seeds is still poorly understood. In particular, more research is needed to assess the likelihood of seed-borne fungi being transmitted to the seedlings and spreading and causing impact in the new environment.

Distribution, causal agents, and infection dynamic of emerging ink disease of sweet chestnut in Southern Switzerland - Simone Prospero; Malve Heinz; Eva Augustiny; Ying‐Yu Chen; Juanita Engelbrecht; Marina Fonti; Aliona Hoste; Beat Ruffner; Romina Sigrist; Noelani van den Berg; Patrick Fonti (Environmental Microbiology, 2023)
Emerging diseases caused by both native and exotic pathogens represent a main threat to forest ecosystems worldwide. The two invasive soilborne pathogens Phytophthora cinnamomi and Phytophthora × cambivora are the causal agents of ink disease, which has been threatening Castanea sativa in Europe for several centuries and seems to be re‐emerging in recent years. Here, we investigated the distribution, causal agents, and infection dynamics of ink disease in southern Switzerland. A total of 25 outbreaks were identified, 19 with only P . cinnamomi , 5 with only P . × cambivora , and 1 with both species. Dendrochronological analyses showed that the disease emerged in the last 20–30 years. Infected trees either died rapidly within 5–15 years post‐infection or showed a prolonged state of general decline until death. Based on a generalized linear model, the local risk of occurrence of ink disease was increased by an S‐SE aspect of the chestnut stand, the presence of a pure chestnut stand, management activities, the proximity of roads and buildings, and increasing annual mean temperature and precipitation. The genetic structure of the local P . cinnamomi population suggests independent introductions and local spread of the pathogen.

Temporal changes in pathogen diversity in a perennial plant–pathogen–hyperparasite system - Lea Stauber; Daniel Croll; Simone Prospero (Molecular Ecology, 2022)
Hyperparasites can affect the evolution of pathosystems by influencing the stability of both pathogen and host populations. However, how pathogens of perennial hosts evolve in the presence of a hyperparasite has rarely been studied. Here, we investigated temporal changes in genetic diversity of the invasive chestnut blight pathogen Cryphonectria parasitica in the presence of its parasitic mycovirus Cryphonectria hypovirus 1 (CHV1). The virus reduces fungal virulence and represents an effective natural biocontrol agent against chestnut blight in Europe. We analysed genome‐wide diversity and CHV1 prevalence in C. parasitica populations in southern Switzerland that were sampled twice at an interval of about 30 years. Overall, we found that both pathogen population structure and CHV1 prevalence were retained over time. The results suggest that recent bottlenecks have influenced the structure of C. parasitica populations in southern Switzerland. Strong balancing selection signals were found at a single vegetative incompatibility ( vic ) locus, consistent with negative frequency‐dependent selection imposed by the vegetative incompatibility system. High levels of mating among related individuals (i.e., inbreeding) and genetic drift are probably at the origin of imbalanced allele ratios at vic loci and subsequently low vc type diversity. Virus infection rates were stable at ~30% over the study period and we found no significant impact of the virus on fungal population diversity. Consequently, the efficacy of CHV1‐mediated biocontrol was probably retained.

Spotting the pests of tomorrow—Sampling designs for detection of species associations with woody plants - René Eschen; Maarten De Groot; Milka Glavendekić; Nikola Lacković; Dinka Matosević; Carmen Morales‐Rodriguez; Richard O Hanlon; Funda Oskay; Irena Papazova; Simone Prospero; Iva Franić (Journal of Biogeography, 2019)
Aim Early warning against potentially harmful organisms of woody plant species can be achieved by sampling sentinel plants in exporting countries. However, it is unclear where sentinel plants can best be located, and how many samples are required and when and how often sampling optimally should take place for the adequate assessment of the biodiversity associated with the target plant species. We aimed to review spatial and temporal factors affecting associate biodiversity of single woody plant species and to develop guidance for the design of global biodiversity sampling studies. Location Worldwide. Taxon Insects and Fungi. Methods Literature about factors affecting the diversity of insects and fungi in association with single plant species on global, regional, local and different temporal scales was reviewed. Case studies of insect and fungal diversity, primarily collected on single plant species, and the cost of collecting and analysing samples from locations around the world were analysed. Results The review of the literature illustrated various factors affecting diversity, and the case studies allowed quantification of the relative impact of some spatial, temporal and financial aspects on captured biodiversity and, thus, illustrate the need to consider all possible factors that may affect the result of the sampling when deciding on a sampling design. Main conclusions Our study illustrates the factors that should be considered when deciding on the location and timing of sampling for sentinel plants, which is important because of the trade‐off between the number of samples and sampling locations needed to detect many of the species which may be potential pests, and the cost of (repeated) sampling in many locations. Decisions about the sampling design must be based on the objective of the sampling, but our recommendations apply irrespective of the targeted plant species or country.

Deciphering the worldwide invasion of the Asian long‐horned beetle: A recurrent invasion process from the native area together with a bridgehead effect - Marion Javal; Eric Lombaert; Tetyana Tsykun; Claudine Courtin; Carole Kerdelhué; Simone Prospero; Alain Roques; Géraldine Roux (Molecular Ecology, 2019)
Retracing introduction routes is crucial for understanding the evolutionary processes involved in an invasion, as well as for highlighting the invasion history of a species at the global scale. The Asian long‐horned beetle (ALB) Anoplophora glabripennis is a xylophagous pest native to Asia and invasive in North America and Europe. It is responsible for severe losses of urban trees, in both its native and invaded ranges. Based on historical and genetic data, several hypotheses have been formulated concerning its invasion history, including the possibility of multiple introductions from the native zone and secondary dispersal within the invaded areas, but none have been formally tested. In this study, we characterized the genetic structure of ALB in both its native and invaded ranges using microsatellites. In order to test different invasion scenarios, we used an approximate Bayesian “random forest” algorithm together with traditional population genetics approaches. The strong population differentiation observed in the native area was not geographically structured, suggesting complex migration events that were probably human‐mediated. Both native and invasive populations had low genetic diversity, but this characteristic did not prevent the success of the ALB invasions. Our results highlight the complexity of invasion pathways for insect pests. Specifically, our findings indicate that invasive species might be repeatedly introduced from their native range, and they emphasize the importance of multiple, human‐mediated introductions in successful invasions. Finally, our results demonstrate that invasive species can spread across continents following a bridgehead path, in which an invasive population may have acted as a source for another invasion.

Using molecular markers to assess the establishment and spread of a mycovirus applied as a biological control agent against chestnut blight - Simone Prospero; Daniel Rigling (BioControl, 2016)

Genetic population structure of the invasive ash dieback pathogen Hymenoscyphus fraxineus in its expanding range - Daiva Burokiene; Simone Prospero; Esther Jung; Diana Marciulyniene; Karin Moosbrugger; Goda Norkute; Daniel Rigling; Vaidotas Lygis; Corine N. Schoebel (Biological Invasions, 2015)

Diversity and ecology of Armillaria species in virgin forests in the Ukrainian Carpathians - Tetyana Tsykun; Daniel Rigling; Vitaliy Nikolaychuk; Simone Prospero (Mycological Progress, 2012)

Eight microsatellite markers for Armillaria cepistipes and their transferability to other Armillaria species - Simone Prospero; Esther Jung; Tetyana Tsykun; Daniel Rigling (European Journal of Plant Pathology, 2010)